EFFECTS OF SOCIAL ACTIVITIES ON THE MENTAL HEALTH WELL-BEING IN JAPANESE OLDER ADULTS. (11th November 2018) - Yoshida, H; Ueki, S; Satoh, T; Inuzuka, G; Anzai, S; Shiba, Y; Haga, H
Abstract: This study was conducted to examine the effects of social participation on the mental health well-being in older Japanese population. The subjects were those aged 65–79 years (n=1, 835) who responded to the baseline survey (2013) in Tome, Miyagi Prefecture, Japan. We followed-up1, 259 individuals (68.6 %) for 3 years. We determined whether baseline social activities affected their mental health well-being in 2016 independently from the impact of key confounders (gender, baseline age, instrumental activities of daily living (IADL) using one of three subscales in the TMIG Index of Competence (TMIG-IC), and mental health well-being, using multiple regression analysis. The social activities were measured by the participation and volunteering component of the Social Activity Check Sheet (SACS), score range: 0–6. The component covers participation in six types of social activities, e.g., community clubs or volunteering. Mental health well-being was assessed by using the Japanese version of the WHO-Five Well-being Index (S-WHO-5-J), which reduces the original 6-point scale to a 4-point scale, score range: 0–15. Increase of one point of baseline SACS score increased S-WHO-5-J total score 0.517 in 2016 significantly (P<.001). Also using multiple regression analysis adjusted for gender, baseline age, TMIG-IC, and S-WHO-5-J, increase of one point of baseline SACS score increased S-WHO-5-J total score 0.207 in 2016 significantly (P<.001). This study found that increase of participating in more social activities expand the opportunities to go out and meet others and these could enhance the future mental health well-being in Japanese older adults.